Kinerja Pemerintah Kabupaten Kayong Utara Pasca Pemekaran Daerah - Darmawan, Rizky (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2019)
This study uses a qualitative approach, which aims to describe and analyze the performance of the Kayong Utara Regency after it was expanded in 2007 by optimizing the role and function of the government in the regional expansion. The results of the study show that the expansion of the Kayong Utara Regency was formed by maximizing the DPRD initiative's rights mechanism. Furthermore, after regional expansion, the economic performance and performance of public services in the Kayong Utara Regency always increase every year, while the financial performance of theÂ Kayong Utara Regency is still low. Also, in optimizing the role and function of the government in regional expansion,Â Kayong UtaraÂ Regency implements it with various programs and activities. The program includes Pelayanan Administrasi Terpadu Kecamatan (PATEN) as an Integrated District Administrative Services, Establishment of Perusahaan Daerah Air Minum (PDAM) as a Regional Water Companies, free school policies and 10 Bachelor Programs per village.